Transformation of the Government's Collaborative Innovation Model In Handling Street Children - Basri Rakhman; Indra Wijaya; Ardy Firman Syah (Jurnal Borneo Administrator, 2026)
This study examines the transformation of the government's collaborative innovation model in handling street children, focusing on the TRC Saribattang (Rapid Reaction Team) innovation in Makassar City. It is a team initiated by the government and formed by the Social Service of Makassar City to maximize performance related to handling street children, beggars, and homeless people in Makassar City. This research investigates the relative advantages, compatibility, complexity, trialability,and observability of the TRC Saribattang innovation in the context of street children management. Data was collected from 12 participants involved in street children management in Makassar City. The study analyzed their perceptions of the TRC Saribattang innovation. This qualitative phenomenological study explored Makassar’s TRC Saribattang innovation for handling street children. Results show simplified processes, stronger cross-sector coordination, and improved access to information, with significant reductions in the number of street children. The implementation's complexity is perceived as low. Observability is evident in the reduction of street children, although discrepancies exist between field reality and reported data. Challenges such as resource limitations, social resistance, and institutional coordination barriers persist. The TRC Saribattang innovation presents a simplified and more coordinated approach to managing street children. The findings of this study are based on a limited number of participants in one city and do not include comparisons with other areas. Explore the long-term impact of the TRC Saribattang innovation, investigate strategies to overcome the identified challenges, and examine the applicability of a pentahelix model for a more integrative approach.